Women, work and wages in England, 1600-1850 - Lane, Penelope 1958-; Raven, Neil 1967-; Snell, Keith D. M. 1955- (Boydell Press, 2004)
Women's employment was significant both for its contribution to industrialisation and to family economies; its range and the rewards are explored. Women's work is recognised as fundamental to the industrialization of Britain in many fields. How it was rewarded is the subject of these studies, ranging over time, region, and occupation. Topics discussed here include children under the parish apprenticeship system, women's work for poor law authorities and how it was taken into account by welfare systems, the changing nature of women's work, remuneration and technology in British agriculture, questionsof customary norms governing pay, female employment in many hitherto neglected urban industries, and women and the East India Company. The issues of gendered wages and customary earnings, family economies, regional and rural-urbancontrasts, the impact of technological change, and the links between female work and formal welfare systems, are raised throughout. Contributors STEVE HINDLE, JANE HUMPHRIES, STEVEN KING, PENELOPE LANE, NEIL RAVEN, MICHAEL ROBERTS, PAMELA SHARPE, K.D.M. SNELL, NICOLA VERDON, SAMANTHA WILLIAMS.